ANALYSIS OF THE EFFECT OF CURRENT RATIO AND QUICK RATIO ON RETURN ON ASSETSIN FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Nur Apriani Fatwa; Nurman; Agung Widhi Kurniawan; Anwar; Andi Mustika Amin (Transpublika Publisher, 2023)
Financial analysis is vital for evaluating company performance, aiding stakeholders in making informed decisions. The Current Ratio and Quick Ratio gauge liquidity, while Return on Assets (ROA) assesses profitability. The Food and Beverage industry, encompassing diverse businesses, faces distinct challenges and opportunities due to changing consumer preferences and competition. Analyzing listed Food and Beverage companies on the Indonesian Stock Exchange provides insights into their financial strategies. This study aims to determine the impact of the Current Ratio and Quick Ratio on Return on Assets in companies within the Food and Beverage sub-sector that are listed on the Indonesian Stock Exchange. The study's population comprises Food and Beverage companies that have been listed on the Indonesian Stock Exchange from 2017 to 2021. A total of 12 companies were selected for observation and data analysis. The collected data underwent tests for Normality, Multicollinearity, and Heteroscedasticity. The analysis employed multiple linear techniques. The findings revealed that the Current Ratio has a positive and significant influence on Return on Assets (ROA), while the Quick Ratio has a negative and insignificant impact on Return on Assets (ROA). Additionally, both the Current Ratio and Quick Ratio, when considered simultaneously, exert an influence on Return on Assets (ROA).